Enterotoxinas, biofilm y resistencia a los agentes antimicrobianos de cepas de Staphylococcus coagulasa negativa aisladas de hemocultivos - Sánchez Galvis Dalialba; Colina López Gladis; Valero Leal Kutchynskaya (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2013)
Abstract: Coagulase-negative staphylococci (CNS) have been identified as the etiological agent in various infections and are currently the microorganisms most frequently isolated in blood cultures. However, little is known about the virulence factors produced by CNS that contribute to the pathogenesis of infections caused by these microorganisms. This study was designed to determine the production of staphylococcal enterotoxins, biofilm production and resistance to antimicrobial agents. For this purpose, a total of 48CNS strains isolated from blood cultures at the University Hospital in Maracaibo, Zulia, Venezuela, were studied. Staphylococcal enterotoxins were detected by reversed passive latex agglutination. Biofilm production was assessed in a quantitative assay using a microtiterplate. Susceptibility against antimicrobial agents was tested by the disk diffusion method. Six strains of staphylococci isolates (12.5%) were found to be enterotoxigenic. Of these, 3 strains were positive for staphylococcal enterotoxin D (SED), 2 for SEA and 1 of the isolates was positive for SEB, SEC and SED. Twenty-one isolates (44%) were found to be biofilm producers. A high frequency of resistance was observed with oxacillin (90%), gentamicin (83%) and erythromycin (67%). None of the isolates showed resistance to vancomycin. Taking into consideration that the etiological importance of CNS has often been neglected, the present investigation confirmed that these microorganisms should not be ignored or classified as mere contaminants. Resumen: Staphylococcus coagulasa negativa (SCN) es el microorganismo que se aísla con mayor frecuencia en los hemocultivos. Sin embargo, es poco el conocimiento que se tiene sobre los factores de virulencia producidos por SCN que contribuyen a la patogénesis de las infecciones causadas por estos microorganismos. El presente estudio se realizó para determinar la producción de enterotoxinas estafilocócicas, la producción de biofilm y la resistencia a los agentes antimicrobianos. Con este propósito, un total 48 cepas de SCN aisladas de hemocultivo en el Hospital Universitario de Maracaibo, Zulia, Venezuela fueron estudiadas. Las enterotoxinas estafilocócicas fueron detectadas por aglutinación en látex pasiva reversa. La producción de biofilm fue evaluada por un ensayo cuantitativo usando microplacas. La susceptibilidad contra los agentes antimicrobianos fue probada por el método de difusión del disco. Seis cepas (12,5%) aisladas de estafilococos fueron enterotoxigénicas. De estas, 3 fueron positivas para enterotoxina estafilocócica D (EED), 2 para enterotoxina estafilocócica A (EEA) y 1 de los aislamientos fueron positivos para enterotoxina estafilocócica B (EEB), enterotoxina estafilocócica C (EEC) y EED. Veintiuno de los aislamientos (44%) fueron productores de biofilm. Alta frecuencia de resistencia fue observada contra oxacilina (90%), gentamicina (83%) y eritromicina (67%). Ningún aislamiento mostró resistencia a vancomicina. Teniendo en cuenta que la importancia etiológica de SCN a menudo ha sido ignorada, la presente investigación confirmó que estos microorganismos no deben ser ignorados o clasificados como contaminantes.